2010
DOI: 10.1111/j.1469-0691.2009.02937.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of influenza immunization in adult cancer patients in Taiwan

Abstract: The aim of this study was to investigate the efficacy of the influenza vaccine among cancer patients in Taiwan. We determined the effect of immunization on the following outcomes of disease: hospitalizations, emergency department visits, hospital outpatient visits, physician office visits, and deaths. Cost-effectiveness was analysed from the perspectives of the healthcare system and society. A decision tree was used, with estimates of disease burden and costs based on data from published and unpublished source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…All but one study 39 reported the primary outcomes (item 11); only three (15%) 30,36,38 did not explain the methods used to assess health status (item 12). Of the 14 papers which clearly explained these methods, 10 (71.4%) 2,3,27,29,33,37,[39][40][41][42] also provided the details of the subjects from whom evaluations were obtained (item 13). Ten studies (50%) [27][28][29][30][34][35][36]39,41,42 did not report separately the productivity changes (item 14), and in the papers where costs and benefits were not discounted, no explanation was given except for one study 40 (item 25).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All but one study 39 reported the primary outcomes (item 11); only three (15%) 30,36,38 did not explain the methods used to assess health status (item 12). Of the 14 papers which clearly explained these methods, 10 (71.4%) 2,3,27,29,33,37,[39][40][41][42] also provided the details of the subjects from whom evaluations were obtained (item 13). Ten studies (50%) [27][28][29][30][34][35][36]39,41,42 did not report separately the productivity changes (item 14), and in the papers where costs and benefits were not discounted, no explanation was given except for one study 40 (item 25).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 16 out of 20 studies (80%) [1][2][3][26][27][28][29][30][31][32][34][35][36][37]40,41 were cost-effectiveness analyses (CEA) whereas four (20%) 33,36,39,41 were cost-benefit analyses (CBA). Regarding effectiveness measures, eight studies (40%) 1,[26][27][28][29]31,34,35 used quality adjusted life years (QALYs), three (15%) 32,34,38 used life years gained (LYG) and all the others chose cases of influenza, hospitalizations, influenza-related complications and deaths averted ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a campaign leveraging social media platforms such as Facebook, YouTube, and blogs was used to induce behavioral changes (17). An increased influenza vaccination rate was related to a reduction in hospital admissions and a decrease in hospitalization cost for cancer survivors (18). We analyzed the frequency pattern of influenza according to time.…”
Section: Discussionmentioning
confidence: 99%